The Manifestation of Hegemonic Masculinity in The Characters of Santa Monica Studio’s God of War (2018) - Marcellino Rizky Putra Himawan; lynda susana widya ayu fatmawaty; Rosyid Dodiyanto (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
This research entitled “The Manifestation of Hegemonic Masculinity in The Characters of Santa Monica Studio’s God of War (2018)” aims to figure out how hegemonic masculinity is manifested in the characters of the video game God of War (2018). The primary data is Santa Monica Studio's God of War which was observed with qualitative method. Moreover, the researcher used Connell’s theory of hegemonic masculinity to analyze the traits of hegemonic masculinity through the characters. This research also uses characterization to further examine the characters’ physical attributes and behavior in investigating their masculinities. The findings of this research indicate that hegemonic masculinity is represented through the characters of Kratos, Atreus, Brok, and Sindri. Using the above theories, the researcher found that those characters’ dialogues, actions, and behavior demonstrate hegemonic masculinity. Another important finding is that each character who performs less hegemonic can still show their hegemony through their actions and speeches. It is also discovered, to an extent that the personalities and the degree of hegemonic masculinity of the characters stem from their respective backgrounds